Evolution and development of the mammalian jaw joint: Making a novel structure. Issue 1 (11th December 2022) - Anthwal, Neal; Tucker, Abigail S.
Abstract: A jaw joint between the squamosal and dentary is a defining feature of mammals and is referred to as the temporomandibular joint (TMJ) in humans. Driven by changes in dentition and jaw musculature, this new joint evolved early in the mammalian ancestral lineage and permitted the transference of the ancestral jaw joint into the middle ear. The fossil record demonstrates the steps in the cynodont lineage that led to the acquisition of the TMJ, including the expansion of the dentary bone, formation of the coronoid process, and initial contact between the dentary and squamosal. From a developmental perspective, the components of the TMJ form through tissue interactions of muscle and skeletal elements, as well as through interaction between the jaw and the cranial base, with the signals involved in these interactions being both biomechanical and biochemical. In this review, we discuss the development of the TMJ in an evolutionary context. We describe the evolution of the TMJ in the fossil record and the development of the TMJ in embryonic development. We address the formation of key elements of the TMJ and how knowledge from developmental biology can inform our understanding of TMJ evolution. Abstract : This review describes the evolution of the novel mammalian novel jaw joint (temporomandibular joint [TMJ]) in the fossil record and the development of the TMJ in embryonic development. It addresses the formation of key elements of the TMJ and how knowledge from developmental biology can inform the understanding of TMJ evolution.